2009
DOI: 10.2337/dc08-2196
|View full text |Cite
|
Sign up to set email alerts
|

The Second-Meal Phenomenon in Type 2 Diabetes

Abstract: OBJECTIVEIn health, the rise in glucose after lunch is less if breakfast is eaten. We evaluated the second-meal effect in type 2 diabetes.RESEARCH DESIGN AND METHODSMetabolic changes after lunch in eight obese type 2 diabetic subjects were compared on 3 days: breakfast eaten, no breakfast, and no breakfast but intravenous arginine 1 h before lunch.RESULTSDespite comparable insulin levels, the rise in plasma glucose after lunch was considerably less if breakfast had been eaten (0.68 ± 1.49 vs. 12.32 ± 1.73 vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
100
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 13 publications
12
100
5
Order By: Relevance
“…The prolonged elevation of plasma FFA levels triggered by the extension of the overnight fast on the NoB day correlated with reduced early insulin release, higher glucose, and less suppressed glucagon and FFA levels after lunch and dinner. A similar positive correlation was observed between FFA and glucose levels after lunch in people with and without diabetes when breakfast was omitted (17)(18)(19). Acute elevation of FFA by intravenous infusion or omission of breakfast has been reported to cause inhibition of insulin-stimulated muscular glucose transport.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The prolonged elevation of plasma FFA levels triggered by the extension of the overnight fast on the NoB day correlated with reduced early insulin release, higher glucose, and less suppressed glucagon and FFA levels after lunch and dinner. A similar positive correlation was observed between FFA and glucose levels after lunch in people with and without diabetes when breakfast was omitted (17)(18)(19). Acute elevation of FFA by intravenous infusion or omission of breakfast has been reported to cause inhibition of insulin-stimulated muscular glucose transport.…”
Section: Discussionsupporting
confidence: 60%
“…Although omission of breakfast has been demonstrated to be associated with a higher glycemic response after a liquid preload (16) or lunch in healthy individuals (17) and in individuals with type 2 diabetes (10,18,19), postprandial glycemia after other meals ingested later during the day has never been assessed. A recent study showed that breakfast skipping resulted in a higher postprandial glycemic response after lunch and dinner in healthy individuals (20).…”
mentioning
confidence: 99%
“…Degree of fasting serum FFA reduction from the baseline level at 24 weeks in the attained group of the present study was similar to that in the above report. Interestingly, Taylor et al observed a positive correlation between the preprandial serum FFA level and postprandial plasma glucose for 4 hours (AUC-PG 0-4h ) in diabetic patients [16]. Therefore, suppression of fasting FFA by Gla may contribute to improvement of postprandial plasma glucose excursion.…”
Section: Appendixmentioning
confidence: 99%
“…These findings contradict those of Axelsen et al [40] who found that carbohydrates in the form of uncooked starch (slow digesting starch) consumed as an evening meal improved glycemic response in individuals with type 2 diabetes to a breakfast meal compared to white bread. Jovanovic et al [41] also found that in individuals with type 2 diabetes, eating breakfast can lower PPGR to a lunch meal compared to not eating breakfast. They also reported that while eating breakfast did not influence insulin levels in individuals with type 2 diabetes, it did suppress FFA levels, which correlated with glucose AUC values.…”
Section: Second Meal Effect and Type 2 Diabetesmentioning
confidence: 98%